Contribution of Adipose Tissue Oxidative Stress to Obesity-Associated Diabetes Risk and Ethnic Differences: Focus on Women of African Ancestry - Pamela A. Nono Nankam; Télesphore B. Nguelefack; Julia H. Goedecke; Matthias Blüher (MDPI AG, 2021)
Adipose tissue (AT) storage capacity is central in the maintenance of whole-body homeostasis, especially in obesity states. However, sustained nutrients overflow may dysregulate this function resulting in adipocytes hypertrophy, AT hypoxia, inflammation and oxidative stress. Systemic inflammation may also contribute to the disruption of AT redox equilibrium. AT and systemic oxidative stress have been involved in the development of obesity-associated insulin resistance (IR) and type 2 diabetes (T2D) through several mechanisms. Interestingly, fat accumulation, body fat distribution and the degree of how adiposity translates into cardio-metabolic diseases differ between ethnicities. Populations of African ancestry have a higher prevalence of obesity and higher T2D risk than populations of European ancestry, mainly driven by higher rates among African women. Considering the reported ethnic-specific differences in AT distribution and function and higher levels of systemic oxidative stress markers, oxidative stress is a potential contributor to the higher susceptibility for metabolic diseases in African women. This review summarizes existing evidence supporting this hypothesis while acknowledging a lack of data on AT oxidative stress in relation to IR in Africans, and the potential influence of other ethnicity-related modulators (e.g., genetic-environment interplay, socioeconomic factors) for consideration in future studies with different ethnicities.